2016
DOI: 10.1016/j.jcv.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Sapovirus prevalence in children less than five years of age hospitalised for diarrhoeal disease in South Africa, 2009–2013

Abstract: Word count abstract: 248Word count article: 2500 2 Highlights:Sapovirus was detected in children hospitalised with acute diarrhoea and in deaths Sapoviruses are common in males, in the second year of life during summer and autumn Factors associated with SaV detection included overcrowding and norovirus infectionsHIV-infected children with SaV had bloody stool and poor access to sanitation Abstract:Background: Although sapovirus (SaV) has been detected in 2.2% to 12.7% of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Co-infections included adenovirus (AdV), astrovirus, bocavirus, norovirus (NoV) GI, NoV GII or rotavirus (RV) [21]. The most frequent co-infection was AdV (43%), followed by NoV GII and RV in 21% of specimens each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infections included adenovirus (AdV), astrovirus, bocavirus, norovirus (NoV) GI, NoV GII or rotavirus (RV) [21]. The most frequent co-infection was AdV (43%), followed by NoV GII and RV in 21% of specimens each.…”
Section: Resultsmentioning
confidence: 99%
“…As part of the ongoing Rotavirus Sentinel Surveillance Programme (RSSP), all specimens were screened for SaV and other enteric viruses [21]. Specimens were collected from children younger than six years old who were hospitalised with gastroenteritis in four provinces of SA (GP; KwaZulu Natal, KZN; Mpumalanga, MP and the Western Cape, WC).…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
“…In Brazil, 18.6% of fecal samples and 36.3% of nasopharyngeal swab samples were detected SaV‐positive from 102 hospitalized children with symptoms of acute gastroenteritis . More importantly, it was reported that 11.4% (9 of 79) diarrheal deaths of children were caused by SaV infection in South Africa …”
Section: Discussionmentioning
confidence: 99%
“…Sapovirus is a member of the Caliciviridae family that worldwide is responsible for 2.2–12.7% of gastroenteritis and has been reported in more than 35 countries [35]. Incubation period is from 1 to 4 days, and there is a median of 6 days of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sapovirus has been studied significantly less than other more common Caliciviridae like norovirus. The clinical presentation of nonbloody diarrhea and vomiting is generally milder than seen with rotavirus or norovirus, but hospitalizations and deaths have been reported [5], particularly in rural areas without running water and in immunocompromised children [3]. PCR assays are the best current method for detection of viral strains [7].…”
Section: Discussionmentioning
confidence: 99%